Jackson solved the problem 3x-8=2(2x-7) using the following steps: STEP 1: Use Distributive Property to get 3x-8=4x-14 STEP 2: Use Addition Property of Equality to get 3x = 4x-14+8 STEP 3: Combine Like Terms to get 3x = 4x-6 STEP 4: Use Subtraction Property of Equality to get 3x-4x= -6 STEP 5: Combine Like Terms to get (-x)=-6 What is the last step? A. Use Property of Equality to get x= (-6) B. Divide both sides by -1 to get x=6 C. Divide both sides by -1 to get x= (-6) D. Use Multiplication Property of Equality to get x=6

1 answer

To solve for \( x \) from the equation \((-x) = -6\), the last step is to divide both sides by -1.

Doing so results in:

\[ x = 6 \]

So, the correct answer is:

B. Divide both sides by -1 to get x=6.

Similar Questions
  1. Multiple Choice QuestionJackson solved the problem 3x-8=2(2x-7) using the following steps: STEP 1: Use Distributive Property to
    1. answers icon 1 answer
  2. Jackson solved the problem 3x-8=2(2x-7) using the following steps:STEP 1: Use Distributive Property to get 3x-8=4x-14 STEP 2:
    1. answers icon 4 answers
  3. Is this correctOrder the steps for solving the equation: 2x−5=3(4x+5) (8 points) 2x−5=3(4x+5) Step 1: Distributive Property
    1. answers icon 3 answers
    1. answers icon 1 answer
more similar questions